Position of an expert panel on diagnosis of treatment of irritable bowel syndrome - Babicki, Mateusz; Mastalerz-Migas, Agnieszka; Stolarczyk, Magdalena; Waśko-Czopnik, Dorota; Wichniak, Adam (Family Medicine & Primary Care Review, 2023)
Irritable bowel syndrome is a significant health problem that can affect up to 11% of the general population. The problem is far more common among women and young people, especially in their thirties. The aetiology of the disease is not fully understood, but it is now thought that dysregulation of the gut-brain axis may be one of the causes. In addition, psychogenic factors, genetics and dietary habits have been attributed a role in the development of the disease. The diagnosis of the disease is based on the clinical picture and the exclusion of other organic causes that may lead to clinical symptoms. According to the Rome IV criteria, diagnosis of IBS is possible when recurrent abdominal pain is found, occurring at least once a week, for the last 3 months. The pain must be accompanied by at least 2 of the following criteria: it is associated with a bowel movement, with a change in the frequency of bowel movements or with a change in the consistency of the stool. Irritable bowel syndrome is a chronic, recurrent condition, with varying frequency of exacerbations and quiescence, dependent on a number of factors. As no clear aetiology has been established to date, we therefore have no causal treatment and no effective and lasting cure. In this situation, treatment must be comprehensive, involving non-pharmacological management related to changes in lifestyle and eating habits and, in the absence of adequate therapeutic effects, pharmacological treatment. Pharmacological treatment should be symptomatic, targeting the predominant complaints and types of IBS, and we can reach for muscle relaxants, drugs to stimulate intestinal peristalsis, antidepressants, rifaximin, laxatives, antidiarrheals and drugs for bloating, probiotics and herbal medicines, e.g. peppermint oil.